Lithuania's integration into Europe: Alternatives and choices - Gediminas Vitkus (Politologija, 2025)
In the beginning of the article, the author postulates: "Lithuania's belonging to Europe is unquestionable". Thus, the main prospects for satisfying the national interests - namely, national security, economic welfare of the citizens, and maintenance of national identity - of Lithuania are tightly bound with the appertainance and further integration into the aforementioned area. However, G. Vitkus notifies, that in spite of the expressed wish of Lithuania saying that the country seeks entrance into European political, economic, and security organisations, in 1997, and particularly in summer 1997 in Madrid and in December in Luxembourg, it has finally become apparent that the delineated goals are not to be implemented easily. Nevertheless, the author claims that such a make-up of events is not to be viewed as a defeat. He says: "Postponement of the EU perspective, on the one hand, and ambiguity of the NATO perspective, on the other, have not only provided us with a chance to re-contemplate the vitality of our strategic choice, but has made us alert that Lithuania's integration into Europe cannot limit and confine itself to integration into these two structures. <...> Moreover, NATO and the EU membership ought to be taken not so much as goals but as a means in order to achieve higher goals - the implementation of Lithuania's national interests." The author argues that Lithuania, which pursues the goals of deepening integration with Europe, intensifying its security, and managing the economic welfare of the citizens, must take advantage of "all the remaining" opportunities the contemporary situation sets forth. Thus, in this article, Gediminas Vitkus analyses these opportunities in detail.